Pengaruh Strategi Promosi dan Harga terhadap Kepuasan Konsumen pada Produk Bouket di Desa Curah Tatal Kecamatan Arjasa Kabupaten Situbondo - Shinta Nur Maulida; Sri Ayuda Mujiyanti; Lusi Endang Sri D (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
In an era of globalization and increasingly fierce market competition, companies are required to be more discerning in designing effective marketing strategies to attract and retain consumers. One crucial element of a marketing strategy is promotion, which serves to increase consumer awareness, interest, and preference toward a product or service. In addition, price is also an essential factor that significantly influences purchasing decisions and customer satisfaction. The balance between an effective promotional strategy and appropriate pricing can determine a company’s success in achieving a competitive advantage. In this context, bouquets, which are aesthetically arranged flower compositions, are becoming increasingly popular, particularly for various special occasions such as weddings, birthdays, graduations, and other celebrations. The increasing demand for bouquets reflects the growing consumer interest in symbolic and personalized products that convey emotions and messages. This study aims to analyze the influence of promotion and price on consumers’ purchasing decisions for bouquet products. Using a quantitative approach through surveys and statistical analysis, the research identifies key factors that shape consumer preferences. The findings are expected to contribute to the development of effective marketing strategies that enhance sales performance and strengthen customer loyalty in the bouquet industry.